Correlation between LL-37 Levels and Scoring of Atopic Dermatitis (SCORAD) in Atopic Dermatitis in dr. Saiful Anwar General Hospital Malang - Sasi Purwanti; Santosa Basuki; Herwinda Brahmanti (Published by Faculty of Medicine Universitas Islam Malang, 2017)
ABSTRACT Introduction: Atopic dermatitis (AD) is a chronic, recidive inflammatory skin disease that is associated with hyper-reactivity of the immune response to environmental allergens. LL-37 is an antimicrobial peptide which plays an important role in the pathogenesis of AD. Several studies conducted to find out LL-37 expression on the skin of patients showed varying and contradictory results. Studies aimed to find out the association of LL-37 levels in circulation with AD degree of severity are still very limited. The aim of this study are to determine the relationship between serum LL-37 levels and Scoring Atopic Dermatitis (SCORAD) score and to determine the relationship between serum LL-37 levels and the severity of atopic dermatitis.Method: This study is analytic observational cross sectional study. The subjects are 30 patients with AD who came to Outpatient Care for Dermatovenereology and Outpatient Care for Pediatric Allergy in dr.Saiful Anwar General Hospital (RSSA) Malang and fulfilled the inclusion and exclusion criteria. The subjects are grouped into 2 groups based on AD severity, i.e. mild and moderate-severe based on SCORAD index. The measured variable is serum LL-37 levels with enzyme-linked immunosorbent assay (ELISA) method.Results: The mean serum LL-37 levels are 12.46.7 ng/ml for mild degree AD and 9.46.06 ng/ml for moderate/severe degree AD. Statistical analysis using Pearson parametric statistic test shows no significant correlation (p> 0.05) between serum LL-37 levels and SCORAD score in patients with AD. Serum levels of LL-37 in this study are lower than the normal score in circulation.Conclusions: LL-37 serum levels in AD do not experience an increase and is not related to SCORAD score.Keywords: Atopic Dermatitis, LL-37, SCORAD